2021
DOI: 10.23887/jppsi.v4i1.30048
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Motivasi Belajar Dan Penguasaan Konsep Kimia Pada Topik Hidrolisis Garam Dan Larutan Penyangga Melalui Pembelajaran Inkuiri Terbimbing

Abstract: Penelitian ini bertujuan meningkatkan motivasi belajar dan penguasaan konsep kimia siswa kelas XI IPA5 SMA Negeri 4 Singaraja melalui penerapan model pembelajaran inkuiri terbimbing. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini siswa kelas XI MIPA5 SMA Negeri 4 Singaraja, berjumlah 39 orang dan objek penelitian ini adalah motivasi belajar dan penguasaan konsep siswa. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus; setiap siklus terdiri atas empat tahap meliputi pere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Student motivation used in this study includes four components, attention (Attention), relevance (Relevance), confidence (Confidere), and satisfaction (Satisfaction). Student motivation is a significant factor in mastering the concept (Armalasari et al, 2017;Merta, 2021). This is confirmed by opinion (Riesyaputra et al, 2015) that the success of the level of mastery of the concept is caused by several factors, including high learning motivation, independent learning, freedom of students in asking and expressing opinions, and creativity…”
Section: Discussionmentioning
confidence: 92%
“…Student motivation used in this study includes four components, attention (Attention), relevance (Relevance), confidence (Confidere), and satisfaction (Satisfaction). Student motivation is a significant factor in mastering the concept (Armalasari et al, 2017;Merta, 2021). This is confirmed by opinion (Riesyaputra et al, 2015) that the success of the level of mastery of the concept is caused by several factors, including high learning motivation, independent learning, freedom of students in asking and expressing opinions, and creativity…”
Section: Discussionmentioning
confidence: 92%
“…In general, in the implementation of the learning process starting from elementary education to secondary education, very few learning processes are found that can create and foster learning motivation and the ability to work together in a team or group for their students (Merta, 2021). The learning process that occurs is still limited to the only transfer of knowledge and generally until now is still dominated by the lecture method (Salim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%